A review of virtual reality based training simulators for orthopaedic surgery. Issue 2 (February 2016) - Vaughan, Neil; Dubey, Venketesh N.; Wainwright, Thomas W.; Middleton, Robert G.
Highlights: A current review of training simulators for orthopaedic surgery is presented. Virtual simulators for orthopaedic surgery lag behind other procedures. Developments are required to bring hip simulators up to date with other surgery. There is a gap in the market for a new high fidelity hip replacement simulator. Hip screw and trauma simulators use more advanced VR than hip replacement. Abstract: This review presents current virtual reality based training simulators for hip, knee and other orthopaedic surgery, including elective and trauma surgical procedures. There have not been any reviews focussing on hip and knee orthopaedic simulators. A comparison of existing simulator features is provided to identify what is missing and what is required to improve upon current simulators. In total 11 hip replacements pre-operative planning tools were analysed, plus 9 hip trauma fracture training simulators. Additionally 9 knee arthroscopy simulators and 8 other orthopaedic simulators were included for comparison. The findings are that for orthopaedic surgery simulators in general, there is increasing use of patient-specific virtual models which reduce the learning curve. Modelling is also being used for patient-specific implant design and manufacture. Simulators are being increasingly validated for assessment as well as training. There are very few training simulators available for hip replacement, yet more advanced virtual reality is being used for other procedures such as hip trauma and drilling. Training simulators for hip replacement and orthopaedic surgery in general lag behind other surgical procedures for which virtual reality has become more common. Further developments are required to bring hip replacement training simulation up to date with other procedures. This suggests there is a gap in the market for a new high fidelity hip replacement and resurfacing training simulator.